2017
DOI: 10.3390/su9111979
|View full text |Cite
|
Sign up to set email alerts
|

Fashion Trendsetting, Creative Traits and Behaviors, and Pro-Environmental Behaviors: Comparing Korean and U.S. College Students

Abstract: Abstract:According to Hofstede's theory of cultural dimensions, cultures differ in cultural values and norms; values and norms that may influence differences in trendsetting, creative traits, and behaviors, and pro-environmental behaviors. Further, because men and women have been socialized within particular cultures, gender differences may exist in trendsetting, creative traits and behaviors, and pro-environmental behaviors. Trendsetters have characteristics that are interrelated with creative traits and beha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…The purpose of the eleventh article by Workman et al [72] was to study the cultural differences and values among fashion trendsetters by using Hofstede cultural dimensions. The focus was on college students in South Korea and the United States (US) to see if there were differences between gender and culture in those two countries by testing twelve hypotheses.…”
mentioning
confidence: 99%
“…The purpose of the eleventh article by Workman et al [72] was to study the cultural differences and values among fashion trendsetters by using Hofstede cultural dimensions. The focus was on college students in South Korea and the United States (US) to see if there were differences between gender and culture in those two countries by testing twelve hypotheses.…”
mentioning
confidence: 99%
“…Fashion trendsetting refers to a specific domain in which the general trait of trendsetting may be manifested. Workman, Lee, and Jung [7] found that Chinese fashion trendsetters scored higher on future time orientation than later adopters. Shen, Qian, and Jiang [17] discovered that Chinese consumers who purchased luxury goods compared with those who did not showed differences in cultural orientation.…”
Section: Fashion Trendsettingmentioning
confidence: 98%
“…Fashion trendsetters, the focus of this research, are also trendsetters in other domains. For example, fashion trendsetters have been found to endorse pro-environmental behaviors [7] and sustainable practices in fashion production [10]. Because trendsetters influence decisions of later adopters, trendsetters can make a difference in the fashion industry's mission to be more sustainable [11].…”
Section: Conceptual Framework and Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, the efficiency of retail chain stores was analyzed in relation to the business model prism approach [46,47]. Fourthly, fashion trendsetting, creative traits and behaviors, and pro-environmental behaviors of Korean and American college students in relation to the open innovation education model were compared [48,49]. Fifthly, the relationship between the efficiency, service quality, and customer satisfaction for state-owned commercial banks in China was analyzed in relation to the arts catalyst of creative organizations for the Fourth Industrial Revolution [50,51].…”
Section: Sustainability Of Economic Growth: Combining Technology Marmentioning
confidence: 99%